Thathiq Idārah al Jūdi fī Tarqiyah Maharat al Lughah al 'arabiyah li al Thalabah Jāmi'ah Daru al Salam Gontor - Fadlan Masykura Setiadi (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2022)
"Application of quality management in improving Arabic language skills for Darussalam University students, Gontor" The purpose of this research is to know the quality standards applied by Darussalam University (UNIDA) Gontor in order to improve the Arabic language skills of UNIDA Gontor students through the implementation of a quality improvement management system. The results of this research seen from the aspect of the quality standard of learning Arabic at UNIDA Gontor have significant differences in terms of teaching materials, cognitive abilities and learning methods used, namely: (1) In terms of teaching materials, it aims to make students able to master the four language skills (mahārah al-lughawiyah) and coupled with the ability to translate, almost 90% of the material taught uses Arabic in the learning process (2) In terms of cognitive abilities, the abilities that must be achieved by students at UNIDA Gontor are at least the level of understanding (understanding), while for the highest level is the ability to innovate or create (create). (3) In terms of the learning methods used in the Arabic learning process, it varies depending on the objectives and the material being taught, but the methods commonly used by lecturers are the direct method (at-tharīqah al-mubāsyarah) and the audio-lingual method (at-tharīqah as-sam'iyah as-syafahiyah) by using Arabic as a communication tool and studying the kitab kuning.